Representing a Coherent Brand out of Incommensurate Goals - Liang, Jingwun; Stack, Michelle (Comparative and International Education / Éducation comparée et internationale, 2022)
Through its website, Facebook, and Weibo page, the University of British Columbia (UBC) states its commitment to being a top-ranked and equitable institution. Using multimodal critical discourse analysis (MCDA), we examined differences across the three platforms and found episodic attention to anti-racism and truth and reconciliation with Indigenous Peoples on ubc.ca; however, this attention was absent on UBC’s Weibo page and less evident on its Facebook page. Conversely, statements concerning UBC’s rankings were consistent and frequent across the three platforms. We draw on the concept of mediatization to analyze how time and online spatial separation of information create an illusion of a coherent narrative that encompasses the incommensurate goals of being a more equitable university while also being top-ranked, particularly to students from China. We conclude with the importance of providing prospective international students with an understanding of the place and sociopolitical and historical context in which they hope to study.